Level of income and use of credit cards in Peru - Rodriguez Cairo, Vladimir (2020)
Objective: Determine if the income level explains the use of credit cards in Peru. Method: A Logit model was used to estimate the probability of use credit cards on those persons who have a card. Results: The Income has a positive effect and statistically significant on credit card use, however, in some areas, as the food spend, it doesn’t observe significant differences in the credit card use related to monthly work income. Conclusions: The population with lower income tends to use the credit card in equal proportion as the higher income segments for certain expenses.